2007
DOI: 10.3168/jds.s0022-0302(07)71595-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultra-High Pressure Homogenization on Microbial and Physicochemical Shelf Life of Milk

Abstract: The effect of ultra-high pressure homogenization (UHPH) on microbial and physicochemical shelf life of milk during storage at 4 degrees C was studied and compared with a conventional heat preservation technology used in industry. Milk was standardized at 3.5% fat and was processed using a Stansted high-pressure homogenizer. High-pressure treatments applied were 100, 200, and 300 MPa (single stage) with a milk inlet temperature of 40 degrees C, and 200 and 300 MPa (single stage) with a milk inlet temperature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
150
1
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(180 citation statements)
references
References 22 publications
(60 reference statements)
18
150
1
8
Order By: Relevance
“…Similar results have been obtained when applying the same homogenization pressures to soymilk or cow milk [27,30]. A previous study of the present authors showed that although pressures of up to 200 MPa were effective in decreasing the droplet size of emulsions with 4 g WPI/100 g (w/v) and 20 g/100 g of oil content, increasing the pressure to 300 MPa tended to increase the droplet size [23].…”
Section: Droplet Size Distributionsupporting
confidence: 70%
“…Similar results have been obtained when applying the same homogenization pressures to soymilk or cow milk [27,30]. A previous study of the present authors showed that although pressures of up to 200 MPa were effective in decreasing the droplet size of emulsions with 4 g WPI/100 g (w/v) and 20 g/100 g of oil content, increasing the pressure to 300 MPa tended to increase the droplet size [23].…”
Section: Droplet Size Distributionsupporting
confidence: 70%
“…3A) are aggregated, while in that which has been UHPH-treated (Fig 3A), not only are the fat globules non-aggregated but they are also distributed, forming a kind of network that enhances physical stability. Sometimes homogenization pressures are also capable of reducing the microbial load of the product prior to the thermal treatment, if they are greater than 200 MPa (N. Cruz et al, 2007;Pereda, Ferragut, Quevedo, Guamis, & Trujillo, 2007;ValenciaFlores et al, 2013). Despite the advantages, this emergent technology is being only used in a laboratory and pilot-scale due to the high investment costs.…”
Section: Nut Milk Processingmentioning
confidence: 99%
“…Vegetative forms of yeasts and moulds are most pressure sensitive compared to their spores (Smelt 1998) and results in 99.99% of reduced activity of psychrotrophics, lactococci and total bacterial count (Pereda et al 2007) alongwith reduction in yeast and mould growth (Daryaei et al 2006). Vachon et al (2002) revealed that dynamic high pressure treatment inactivates 3 major food pathogens (Listeria monocytogenes LSD 105-1, Escherichia coli O157:H7 ATCC 35150 and Salmonella enteritidis ATCC 13047) present in milk.…”
Section: Application Of Hhp In Dairy Industrymentioning
confidence: 99%